Withholding Taxes, Compliance Cost, and Foreign Portfolio Investment - Jacob, Martin; Todtenhaupt, Maximilian (The Accounting Review, 2023)
ABSTRACT We examine the effect of compliance frictions in reclaiming foreign withholding tax overpayments on foreign portfolio investment (FPI) using data on bilateral FPI around the globe and U.S. institutional investors’ foreign holdings. Exploiting variation in withholding tax overpayments for 36 investor countries and 110 issuer countries, we find that withholding tax overpayments adversely affect FPI because of the high compliance costs to international investors in claiming foreign tax credits. Cross-sectional tests further show that the adverse effect of withholding tax overpayments on FPI is reduced when compliance costs in claiming these overpayments from foreign countries are lower. Our results indicate that eliminating most of the compliance costs in the reclaim process by implementing a relief at the source mechanism could increase FPI by about 7.6 percent. JEL Classifications: D25; G11; G25; H20; H24.